(untitled) (Research, Society and Development, 2020)
This paper aims to analyze the influence of family background on the performance of students with disabilities in integrated technical education at the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN). The variables chosen for the study were: type of school, father’s education, mother’s education, family income, gender and ethnicity. The methodology is applied in an exploratory, descriptive and quantitative way. As for the samples, data from the Unified Public Administration System (SUAP) of 64 students with disabilities from IFRN were used. Simple linear regression was applied, using SPSS software version 24. With the compilation of data in the regression software, the results showed that the higher the family income of a student with a disability, the higher the Income Index of the student (IRA) and according to the data, the student’s performance is influenced by the mother’s education. As for ethnicity, students who are self-declared black, mixed race and indigenous, presented an I.R.A. lower than white students. The type of school of origin was also studied and the results showed that students who come from public schools have a deficit in I.R.A. compared to students in private schools.